Asuhan Keperawatan Pada Lansia dengan Hipertensi di Desa Lamglumpang Kota Banda Aceh - Febriana, Dara; Khairani, Khairani; Khairani, Nurul; Mardhiah, Ainal; Taufik, Taufik (Poltekkes Kemenkes Aceh, 2024)
Background: Hypertension is a state of change where blood pressure increases chronically. The hypertensive disease is often called a “silent killer” because it can appear without symptoms or warning signs, so many people fail to recognize it. Purpose: To provide an overview of nursing care for patient, who suffers from hypertension. Methods: The research method used is descriptive qualitative with a case study approach described through the nursing process. The implementation of nursing interventions was carried out for 5 days and the main problems were measured using the Numeric Rating Scale (NRS). Results: The result showed that client has an increased understanding of non-pharmacological pain deep breath relaxation techniques, and there is a decrease in pain scale form 4 NRS to 0 NRS. For the diagnoses of ineffective health management, the result showed increased knowledge related to hypertension, warm water foot baths, and the application of dietary patterns. Thus, it resulted in a decrease in blood pressure, which was 9/15 mmHg. Conclusion: After implementing warm water foot soak therapy for 5 consecutive days, it can be concluded that warm water foot soak therapy is very influential in controlling and reducing the client's blood pressure. Warm water foot soak therapy shows effective results where blood pressure is reduced by 9/10 mmHg.